Tongklek Ethnomusicology in Pesantren: A Case Study at Pondok Pesantren Sunan Drajat 7 Tuban - Moh Abdulloh Hilmi; Moh Muflih; M Mundzir; M Asror Yusuf (LPPM Universitas KH. A. Wahab Hasbullah, Jombang, Indonesia, 2025)
Tongklek, commonly known as a traditional art form using kentongan percussion instruments, has become integrated into dakwah practices at Pondok Pesantren Sunan Drajat 7 Tuban. This study examines the extent to which tongklek music at the pesantren has merged with the social and cultural life of the surrounding community. This research is a field study conducted through direct observation of tongklek artistic practices at Pondok Pesantren Sunan Drajat 7. The study employs Timothy Rice’s ethnomusicological framework. The findings indicate that tongklek music has developed into a social practice cultivated by the santri. The selection of specific religious songs reflects a fusion of religious identity and cultural meaning within the music. Tongklek art at the pesantren demonstrates how traditional music can transform and play a significant role in strengthening social and cultural relationships within the community.